ANALYSIS ON CONSTRAINTS OF LOCAL AND NATIONAL LANGUAGE USING IN LATE ADOLESCENCE IN NORTH SUMATRA - Yoga, Husni Rahman; Malau, Nadya Aulia (PEOPLE: International Journal of Social Sciences, 2020)
Indonesia is famous for its rich and varied language culture which is influenced by the cultural backgrounds, ethnicities, and customs of each region. From 718 local languages in Indonesia, there are 5 of them in North Sumatra, namely: Batak, Nias, Minang, Java, and Malay language. Therefore, national language is needed to unite the various tribes, especially for late adolescence in their daily activities both those from city to village or from village to city. This difficulty was the basis of our research to analyze the constraints of using two languages (local and national) in late adolescence in North Sumatra, Indonesia. This research used qualitative research with interview and observation techniques for 5 late-adolescent samples consisting of 2 people from city to village; 3 people from the village to city conducted for 1 month from 10 November to 10 December 2019 by looking at their daily lives in adapting to an environment that is not their original place. As a result, researchers found the constraints in the use of local and national language in North Sumatra, such as basic sentence patterns, language intonation, dialect, cultural background, and habits.